Launch Country Responsibility for Space Debris Under International Space Law - Markus Haris Saputra Tampubolon; Jeffry A.Ch. Likadja; Gerald Aldytia Bunga (Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of this study is to examine the legal implications of the growth in space debris produced by launching countries' liability for space debris under International Space Law. This study highlights the normative juridical procedure and employs a qualitative research strategy. The framework of this research departs from the concept of state responsibility for space debris, state regulation of space debris, the concept of fault liability to the owner of space objects, the concept of joint liability of owners of space objects from more than one country or legal entity, and the category of problems in space debris objects that impede the launch of new satellites, disrupt the function of active satellites in space orbit, and cause loss and damage in space and Earth. The findings revealed that the state's responsibility for space debris under space law has not been maximized because there are various difficulties that prevent the application of international law